Peran Unit Airport Operation Land Side dan Terminal dalam Pengalokasian Baggage Conveyor Belt di Terminal Internasional Bandar Udara I Gusti Ngurah Rai Bali - Ersa Bayu Al Fiqih (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
I Gusti Ngurah Rai International Airport is one of the airports that is the entry point for tourists or foreign tourists who want to visit Bali, because of its diverse tourist destinations. The AOLT or Airport Operation Land Side and Terminal unit is one of the units in charge of services at I Gusti Ngurah Rai Airport, Bali. The task of the AOLT unit is to supervise all operational activities, especially on the land side, which includes all passenger arrival and departure activities, facilities and infrastructure in the airport terminal, including in the baggage claim area, namely the allocation of the baggage conveyor belt so that it can operate smoothly in accordance with the Decree. Directors of PT. Angkasa Pura I (Persero) regarding Terminal Operational Standards at Airports managed by PT. Angkasa Pura I (Persero). Based on the author's observations when carrying out OJT in September 2022 at the Airport Operation Land Side unit and I Gusti Ngurah Rai Airport Terminal, Bali, there was a problem of damage to the baggage conveyor belt at the international terminal, resulting in a buildup of baggage in the baggage claim area at the international terminal at Airport I Gusti Ngurah Rai Bali. The purpose of this research is to determine the role of Airport Operation Land Side and Terminal in allocating baggage conveyor belts at the international terminal of I Ngurah Rai International Airport, Bali and to find out how to deal with baggage accumulation at the international terminal of I Ngurah Rai International Airport, Bali. This study uses a qualitative method. This research was conducted at I Gusti Ngurah Rai Airport, Bali, which was carried out in August 2023. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data reduction, data analysis, and conclusions. The data validity technique used is source triangulation.Research results based on the role of the AOLT unit in the MOS (manual of standards) show that: (1) In allocating conveyor belts, the AOLT Unit must consider various factors such as flight schedules, aircraft type, country of origin airport, and facility readiness. The AOLT unit interacts with airlines, airport managers and technical units. (2) The solution if baggage piles up at the I Gusti Ngurah Rai International Airport Terminal in Bali is to update the arrival schedule and allocate conveyor belts regularly. The AOLT Unit can coordinate with other units such as AMC, Menikal and AOCH to provide comfortable services to passengers. , and improve facilities and infrastructure in the terminal and land side areas.